Therapeutic potential of mesenchymal stem cell-derived exosomes in skeletal diseases - Yang, Xiaobo; Zhang, Shaodian; Lu, Jinwei; Chen, Xiaoling; Zheng, Tian; He, Rongxin; Ye, Chenyi; Xu, Jianbin (Frontiers in Molecular Biosciences, 2024)
Skeletal diseases impose a considerable burden on society. The clinical and tissue-engineering therapies applied to alleviate such diseases frequently result in complications and are inadequately effective. Research has shifted from conventional therapies based on mesenchymal stem cells (MSCs) to exosomes derived from MSCs. Exosomes are natural nanocarriers of endogenous DNA, RNA, proteins, and lipids and have a low immune clearance rate and good barrier penetration and allow targeted delivery of therapeutics. MSC-derived exosomes (MSC-exosomes) have the characteristics of both MSCs and exosomes, and so they can have both immunosuppressive and tissue-regenerative effects. Despite advances in our knowledge of MSC-exosomes, their regulatory mechanisms and functionalities are unclear. Here we review the therapeutic potential of MSC-exosomes for skeletal diseases.